2016
DOI: 10.24280/ape.v1i1.64
|View full text |Cite
|
Sign up to set email alerts
|

Compreensão De Leitura E Uso De Estratégias De Aprendizagem: Estudo Correlacional

Abstract: READING COMPREHENSION AND USE OF LEARNING STRATEGIES: CORRELATIONAL STUDYABSTRACT: This study aimed to relate measures assessing evaluation of reading comprehension and learning strategies. Attended 224 primary school students, aged between 7 and 11 years, 113 boys and 111 girls enrolled in the third, fourth and fifth year in a public school in the state of São Paulo. The instruments used were two structured texts according to traditional standards of Cloze technique and the Scale of Learning Strategies Evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
1
1
0
6
Order By: Relevance
“…As to the correlation found between the metacognitive strategy and the Cloze test, this result was shown by Fletcher et al (2009), Joly and Dias (2012), Lima and Santos (2016) and Soares and Emmerick ( 2013). However, similarly to the study by Lima and Santos (2016) the result was not confirmed in the regression analysis, and it was not possible to verify if one variable could predict the other. In this sense, it would be important for new studies to be performed, with a larger number of subjects, to complement the data that was previously found.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…As to the correlation found between the metacognitive strategy and the Cloze test, this result was shown by Fletcher et al (2009), Joly and Dias (2012), Lima and Santos (2016) and Soares and Emmerick ( 2013). However, similarly to the study by Lima and Santos (2016) the result was not confirmed in the regression analysis, and it was not possible to verify if one variable could predict the other. In this sense, it would be important for new studies to be performed, with a larger number of subjects, to complement the data that was previously found.…”
Section: Discussionsupporting
confidence: 53%
“…Comprehensive reading requires a series of skills and procedures, one of which is the use of learning strategies. The learning strategies can be categorized in many different ways, however in this paper we will use a perspective based on the Theory of Information Processing, in which the learning strategies are seen as mental and behavioral actions and that aid the learning process through cognitive and metacognitive strategies that favor behavioral self-regulation, as well as a more effective learning (Boruchovitch, 1999;Dembo, 1994;Lima & Santos, 2016;Inácio, Oliveira, & Mariano, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Essas estratégias são importantes porque fornecem suporte essencial para a aquisição de satisfatório desempenho acadêmico (Prates, Lima, & Ciasca, 2016). O uso de estratégias possibilita o eficiente armazenamento da informação e sua eficaz recuperação, e, para tanto, é importante que o estudante tenha conhecimento delas e saiba como utilizá-las adequadamente (Lima & Santos, 2016;Oliveira et al, 2017). (Dembo, 1994;Perassinoto et al, 2013;Suehiro, Boruchovitch, & Schelini, 2018).…”
Section: Introductionunclassified
“…Os estudos que abordam a temática concentram-se em outras etapas de ensino, como o ensino fundamental (Costa & Boruchovitch, 2015;Ferraz et al, 2019;Lima & Santos, 2016;Maieski et al, 2017;Perassinoto et al, 2013;Prates et al, 2016;Santos et al, 2018) e ensino superior (Alcará & Santos, 2013;Albuquerque et al, 2016;Beluce & Oliveira, 2016;Castro et al, 2016) Considerando a relevância desses construtos para a avaliação psicoeducacional na busca de indicadores que auxiliem no desenvolvimento do sucesso escolar dos estudantes do ensino médio (Bzuneck & Boruchovitch, 2016;Greene et al, 2004;Inácio, 2018), a presente pesquisa teve como objetivos: 1. caracterizar o nível de motivação para a realização das atividades escolares e identificar em que medida os alunos relatam utilizar estratégias de aprendizagem; 2. correlacionar as subescalas de motivação para aprender e as estratégias de aprendizagem; 3. analisar possíveis diferenças nas pontuações das escalas considerando o sexo e o ano escolar; 4. identificar se a motivação para aprender pode predizer o emprego das estratégias de aprendizagem.…”
Section: Introductionunclassified
“…Contudo, há um predomínio pelas etapas do ensino fundamental (Lima & Santos, 2016;Lopes, et al, 2017;Oliveira et al, 2014;Prates et al, 2016;Perassinoto et al, 2013;Trassi, 2016) e do ensino superior (Alcará & Santos, 2013;Beluce & Oliveira, 2016;Marini & Boruchovitch, 2014). Diante disso, pode-se observar uma escassez de produções referentes à etapa do ensino médio (Oliveira, 2010;Maciel, Souza & Dantas, 2015).…”
unclassified